Composition comprising red rice fermentation product and preparation - Ariff, Arbakariya; Ajdari, Zahra; Abdul Manan, Musaalbakri; Kapri, Mohammad Rizal; Mohamad, Rosfarizan; Hamid, Muhajir (2013)
The present invention provides a product of the fermentation of a Monascus strain that can be used as a dietary supplement or as a therapeutic medicament to lower both serum cholesterol and triglyceride levels in mammals. In one aspect, there is provided a composition for treating elevated serum cholesterol and/or triglycerides, wherein the comprising a red rice product containing a polar extract of Monascus purpureus. In a second aspect, there is provided a method of preparing a red rice product by an improved fermentation procedure, the method comprising the steps of: (i) culturing a Monascus purpureus fungi strain in a culture medium comprising rice; (ii) removing the culture medium to provide a solid residue; and (iii) drying the solid residue to form the red rice product. In a third aspect, there is provided a pharmaceutical or nutritional composition comprising the polar extract of red rice product or Monascus purpureus fermented product.